Database Development in Using and Maintaining Machine and its accessories at SMK Muhammadiyah Kartasura and Jatinom Klaten in Community service - Putro, Pramuko Ilmu Purbo; Sarjito, S; Febriantoko, Bambang Waluyo; Darmawan, Agung Setyo (Journal of Community Services and Engagement: Voice of Community (VOC), 2022)
The aim of the program was community service types of application of science and technology byDatabase Creation and Usage Machine Maintenance and its Equipment at Muhammadiyah Kartasura and Jatinom Klaten as Vocational School to support the practicum process in the Muhammadiyah Vocational School laboratory. The implementation method wasbysynchronize basic inventory, then made a data base application by means of machine tools sticking with barcodes on a laboratory scale. With this activity, its will facilitating the implementation of routines and practicum readiness from time to time. Thus at the same time this will add value to the teaching and learning process atSMK which includes 40% theory and 60% practice manufacture.Through this activity it will also add value to their vocation which will bring the world of education and industry much closer, especially in the field of goods assembling and manufacturing.From observations while working with partners, namely SMK Muhammadiyah Kartasura and SMK Muhammadiyah Jatinom Klaten, the obstacle faced is in coaching on the creation of a data base for the use and maintenance or readiness of tools for practice. The process of creating a database of equipment,usage and conditions,this will support the continuity of the practicum process smoothly. The making of this database will be transmitted and will become provision for students primarily for competence in the areaof manufacturing work or for future entrepreneurship. So it is expected from this process, students and teachers get a new way of learning, useful for students and the existence of the SMK in the future, particularly in learning assembly making and thinking steps to control the underlying equipment. Thus the students have enough competence and adaptive when entering the world of work related to the process design based on data collection and monitoring using technology growing of smartphones